A turbulent time: government sources post-2016 presidential election. Issue 1 (19th December 2019) - Kubas, Alicia
Abstract : Purpose: Since the 2016 presidential election, hyper-partisanship has become a regular facet of the political landscape with Democrats and Republicans in increasing conflict. The purpose of this paper is to determine if perception of government sources related to trust and credibility has changed since the 2016 election and if the experiences and strategies of librarians who teach or consult about government information has changed in response to this environment. Design/methodology/approach: A 24-question survey was distributed to garner qualitative and quantitative responses from librarians who teach or consult about government information in an academic environment. A total of 122 responses were used for analysis. Findings: Academic librarians are seeing more concern from patrons about disappearing online government information and wider distrust of government information. Librarians also noticed that the political leanings of students color their perspective around government sources and that librarians also need to keep their political beliefs in check. Respondents emphasized a need for more government literacy and information literacy topics when discussing evaluation of government sources. Research limitations/implications: The data collection only included responses from academic librarians. Further research could include in-depth interviews and look at experiences in various library types. Originality/value: With the timeliness of this topic, there has not been an in-depth investigation into how the Trump administration has changed user trust and perception of government sources from the librarian's point of view. This paper continues the conversation about how librarians can address the growing distrust of government information and give us insight into the effects of a turbulent political climate on government sources.